2022
DOI: 10.1186/s13048-022-00963-9
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and TrKB expression levels in patients with endometriosis and their associations with dysmenorrhoea

Abstract: Background Brain-derived neurotrophic factor (BDNF) is a known regulator of the development and maintenance of chronic pain in various chronic disorders. Together with its high-affinity tyrosine kinase type B (TrKB) receptor, BDNF is extensively expressed in the mammalian female reproductive system. However, BDNF and TrKB expression in different stages of endometriosis and the relationship between the expression of each in ectopic lesions and endometriosis pain remain unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
11
0
2
Order By: Relevance
“…33 Meanwhile, BDNF, together with its high-affinity tyrosine kinase type B (TrKB) receptor, has been linked to the onset of severe female reproductive disorders, including endometriosis. 34 Further, the present investigation pointed out the positive effects of Ye-Jiao-Teng and Chuan-Niu-Xi in preventing the onset of endometriosis. A murine model showed that an extract of Ye-Jiao-Teng could downregulate nitric oxide (NO) and pro-inflammatory cytokines, such as TNF-α and IL-1β, which are key mediators of inflammation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…33 Meanwhile, BDNF, together with its high-affinity tyrosine kinase type B (TrKB) receptor, has been linked to the onset of severe female reproductive disorders, including endometriosis. 34 Further, the present investigation pointed out the positive effects of Ye-Jiao-Teng and Chuan-Niu-Xi in preventing the onset of endometriosis. A murine model showed that an extract of Ye-Jiao-Teng could downregulate nitric oxide (NO) and pro-inflammatory cytokines, such as TNF-α and IL-1β, which are key mediators of inflammation.…”
Section: Discussionsupporting
confidence: 54%
“… 33 Meanwhile, BDNF, together with its high-affinity tyrosine kinase type B (TrKB) receptor, has been linked to the onset of severe female reproductive disorders, including endometriosis. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Згідно з теорією нейроангіогенезу, BDNF, як відомо, є трофічним як для нервів, так і для капілярів [13]. BDNF бере участь у шляхах болю не лише на центральному рівні, відіграючи ключову роль у центральній сенсибілізації при багатьох формах гіпералгезії, але також і на периферії після пошкодження нерва, модулюючи сенсорну нейротрансмісію у ноцицептивному шляху, тому відіграє важливу роль у перебігу ноцицептивного та нейропатичного болю [15,17]. Механізм нейрогенезу при ендометріозі залучає нейротрофіни, такі, як BDNF.…”
Section: г і н е к о л о г і яunclassified
“…За даними останніх досліджень, виявлено підвищення концентрації BDNF у сироватці та плазмі крові у жінок з ендометріозом, асоційованим із тазовим болем і безпліддям, порівняно з контрольними групами [7,[13][14][15]18]. Рівень BDNF у крові пацієнток з ендометріозом позитивно корелює з клінічною стадією ендометріозу, тяжкістю СХТБ та ступенем дисменореї [7,17,19]. Також рівні BDNF у плазмі крові позитивно корелюють із показниками рівня тяжкості болю [14,18,19].…”
Section: г і н е к о л о г і яunclassified
“…Another interesting biomarker, brain-derived neurotrophic factor (BDNF), has been found to be linked with several pathways that are disturbed in women with endometriosis. BDNF is a neurotrophin (26) with a high-affinity to neurotrophic tyrosine receptor kinase 2 (NTRK2) also known as Tropomyosin receptor kinase B (TrKB), and this ligand-receptor pair participates in some aspects of uterine physiology (27). BDNF and NTRK2 were more significantly expressed in the uterus of women with endometriosis compared to disease-free controls (28); BDNF has been found to be dysregulated and overexpressed in ectopic but not in eutopic endometrial tissue.…”
Section: Article Length Targetmentioning
confidence: 99%